2022
DOI: 10.3892/ijo.2022.5360
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification regulates tumor progression and metastasis through EMT (Review)

Abstract: Epigenetics is the study of heritable molecular determinants that are independent of phenotypic features. The epigenetic features include DNA methylation, histone modifications, non-coding RNAs, and chromatin remodeling. In multicellular organisms, the epigenetic state of a cell is critical in determining its differentiation status and its ability to perform its proper function. These processes are now well recognized as being a substantial factor in tumor progression and metastasis. The process through which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 238 publications
(238 reference statements)
0
15
0
1
Order By: Relevance
“…Furthermore, this growing body of evidence has demonstrated that histone deacetylases (HDACs) are linked to the initiation and/or maintenance of repression for DNA hypermethylated genes, and studies have revealed that the simultaneous targeting of both DNA methylation and histone deacetylation leads to additive or synergistic effects to reactivate the aberrantly silenced genes ( Arrowsmith et al, 2012 ). Meanwhile, it has been observed that in the case of histone methylation, methylation of histones H3 and H4 is a very common feature of cancer cells ( Tan et al, 2022 ). Notably, it was reported that DNMT demethylating agents and histone deacetylase inhibitors could be combined to exert antitumor effects ( Zahnow et al, 2016 ; Myasoedova et al, 2019 ).…”
Section: Future Outlookmentioning
confidence: 99%
“…Furthermore, this growing body of evidence has demonstrated that histone deacetylases (HDACs) are linked to the initiation and/or maintenance of repression for DNA hypermethylated genes, and studies have revealed that the simultaneous targeting of both DNA methylation and histone deacetylation leads to additive or synergistic effects to reactivate the aberrantly silenced genes ( Arrowsmith et al, 2012 ). Meanwhile, it has been observed that in the case of histone methylation, methylation of histones H3 and H4 is a very common feature of cancer cells ( Tan et al, 2022 ). Notably, it was reported that DNMT demethylating agents and histone deacetylase inhibitors could be combined to exert antitumor effects ( Zahnow et al, 2016 ; Myasoedova et al, 2019 ).…”
Section: Future Outlookmentioning
confidence: 99%
“…DNA methylation, as one of the common epigenetic events, plays a key role in the diagnosis and treatment of tumors ( 40 ). In contrast to other CGRs, ATP7B, NLRP3, and ATP7A were distinctly hypomethylated in multiple cancers, such as BRCA, LUSC, and LUAD.…”
Section: Resultsmentioning
confidence: 99%
“…The overall prognosis for patients with OS is poor because of its high metastatic potential [ 28 ]. EMT is a key mechanism of tumor metastasis, inhibition of which may attenuate cancer metastasis [ 29 ]. In this study, we found that silencing ZCCHC12 slowed down migration of OS cells.…”
Section: Discussionmentioning
confidence: 99%